Production of Biosurfactant from Frangipani Flower Extract (Plumeria rubra) as an Eco-friendly Detergent in a Science Learning Project - T. Liana; E. C. Prima; P. Sinaga; R. Riandi (Journal of Science Education Research, 2023)
This study aims to provide experience to students through experimental activities in making liquid detergent to teach substance material and its changes according to the learning outcomes to be achieved. The research method used is a type of experimental research in the laboratory. Frangipani flower extract (Plumeria rubra) which is used as research material contains saponins that be used as natural surfactants in the manufacture of liquid detergents. Frangipani flower extraction was carried out by maceration using 96% ethanol solvent, the resulting extract was then subjected to a saponin identification test. In this study, it was prepared in 4 different formulations with a comparison of frangipani flower extract of 2 ml (F1), 4 ml (F2), 6 ml (F3), and 8 ml (F4). After that, it was evaluated physically and chemically including organoleptic tests, pH tests, foam stability, and detergency. The results of the saponin test on frangipani flower extract showed positive results, and the results of the chemical physics test were by SNI standards. The most optimum formulation is a liquid detergent with an extract concentration of 4 ml showed an organoleptic test according to SNI standards, a stability test of 85.00%, a pH of 10.30, and detergency showed good results.